Update in Urologic Surgery: Introduction to Robotics - Muhletaler-Maggiolo, Fred (2025)
This is a paper that explains the genesis of robotic technology in general and the reasons why it was developed aswell as its advantages with prior technologies. The analysis makes a concise summary of the most frequent urologic roboticsurgeries in the world and the most salient facts about their developments and current roles. Finally, an explanation offuture directions in the field of robotic surgery is given.